Social Media Use, eHealth Literacy, Knowledge, Attitudes, and Practices Toward COVID-19 Vaccination Among Chinese College Students in the Phase of Regular Epidemic Prevention and Control: A Cross-Sectional Survey - Qin, Ning; Shi, Shuangjiao; Duan, Yinglong; Ma, Guiyue; Li, Xiao; Shen, Zhiying; Zhang, Shuhua; Luo, Aijing; Zhong, Zhuqing (Frontiers in Public Health, 2022)
Background College students are at a high risk of being infected with COVID-19, and they are one of the key population clusters that should be vaccinated. The present study aimed to investigate the knowledge, attitudes, and practices (KAP) toward COVID-19 vaccination among Chinese college students, and to determine the relationships among social media use, eHealth literacy, and KAP toward COVID-19 vaccination among Chinese college students. Methods A cross-sectional survey was conducted by administering questionnaires to evaluate KAP toward COVID-19 vaccination, social media use, and eHealth literacy in one of the groups of Chinese college students. Multiple linear regression analysis was performed to determine the association among social media use, eHealth literacy, and KAP regarding COVID-19 vaccination. Results Among the 3,785 validated questionnaires collected from Chinese college students, male students accounted for 59.74%, and the mean age of the college students was (20.90 ± 3.14) years. More than four-fifths (83.43%) of the college students spent <2 h a week on social media, and the official and public social media were most common social media types. Additionally, the scores for KAP toward COVID-19 vaccination ranging from 0 to 48 among college students were high (39.73 ± 5.58), lowest for knowledge domain (3.07 ± 0.76), and the highest for practice domain (3.47 ± 0.63). Female college students who were in good health status and who spent more time browsing social media, frequently used official and public social media, rarely used aggregated social media, and had a relatively strong self-perception of eHealth literacy and information acquisition of eHealth literacy were more likely to have high levels of KAP regarding COVID-19 vaccination. Conclusions Overall, Chinese college students have excellent KAP toward COVID-19 vaccination. Based on the findings of this study, we recommend that health counseling regarding COVID-19 vaccination should target male students and those with inferior health status. Dissemination of health education regarding COVID-19 vaccination should be purposely conducted, and cooperation with official and public social media platforms should be promoted. Finally, eHealth literacy, which is one of the predictors of the level of KAP regarding COVID-19 vaccination, should be emphasized.